Motus 4: new developments on a web-deployed software for composing real-time audiovisual interactions - Amstalden, Augusto Piato; Tavares, Tiago Fernandes (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação Musical, 2021)
Camera-based audiovisual interactions have been greatly used in art installations. For such, it is often necessary to use specialized hardware and software. This restricts audiovisual installations to areas that can both afford them financially and be physically accessed by the audience. In this work, we present the development of a web-deployed composition tool for audiovisual interactions that runs on the client side and does not require installing any additional software. The tool allows quickly configuring areas for movement capture, and customizing the corresponding audio feedback. Simultaneously, it provides visual feedback that can aid the audience to understand the experience. Consequently, the tool can be used to compose audiovisual interactions that reach a large audience via web. Moreover, its virtual and ubiquitous nature can foster a diversity of artistic explorations related to the remote characteristic of the relationship between audience and artwork.